Active Knowledge-sharing Method: Implementation of Google Earth-based Multimedia As a History Learning Media to Improve Cognitive Ability in High School an Makassar - ., Amirullah; Manda, Darman; Rusli, Nurliani; Arifin, Faizal; Hartono, Yudi (KnE Social Sciences, 2024)
Learning history requires the internalization of principles, information, and abilities related to historical events that are planned and organized to influence and encourage student learning. In this era of globalization and information, the use of Information Technology (IT)-based learning media is a necessity and a demand, however, its implementation is not an easy thing. The implementation of information technology in the learning process is expected to be more interesting, active, and creative in an integrated, systematic, and effective manner per the demands of the skills of this century. Skills are the vision of education to deal with technological advances and the development of various intelligences of students to achieve maximum potential. The implementation of Google Earth-based multimedia as a learning medium using the active knowledge-sharing method in learning Indonesian history is very effective in increasing the cognitive abilities of students at High School an Makassar. The purpose of writing this article is to implement the use of Google Earth-based multimedia as a historical learning media based on Google Earth with the active knowledge-sharing method to improve the cognitive abilities of students at High School an Makassar. The results of writing this article show that the use of Google Earth-based multimedia as a learning medium using the active knowledge-sharing method in Indonesian history subjects has. Keywords: active knowledge sharing, method google earth, learning history